Elemen Smart Library pada Interior Perpustakaan Perguruan Tinggi - Syahida, Arifah Nur; Wulandari, Ratri; Haristianti, Vika (Program Studi Desain Interior Unikom, 2021)
University’s Library is a supporting of academic activities for the achievement of learning objectives, organizing learning for each study program, collections of learning strategies and supporting material for learning evaluation. With the advancement of technology and information, people prefer to search for information through online media without having to look for books in the library. Therefore, it is necessary to increase library facilities through the Smart Library concept which have 4 concepts including smart service, smart place, smart governance, and smart people. By referring to these 4 concepts, it is hoped that the University Libraries in Indonesia, especially in the city of Bandung, can be superior and can improve education for the wider community.